Spirituality as mediator for relationships between nature exposure, connectedness to nature and psychological well-being of school students in Johor Bahru, Malaysia - Md Sahak, Siti Nabihah (2018)
Psychological well-being (PWB) of school students in Malaysia has scarcely been discussed. Excellence in academic achievement is deemed more important compared to their inner needs, which include their PWB. Engagement with nature, through sensory exposure and a sense of connectedness to nature, has found to have a positive effect on PWB. The purpose of this study is to explore the outcomes of nature engagement on the PWB of school students, and the role of spirituality in mediating these variables. A total of 293 Form Four school students in standard secondary school in the Johor Bahru district. The 16-year-olds respondents involved in the study comprised of 178 females, and 115 males. The descriptive and inferential data was analysed by using SPSS 23.0. The respondents completed the survey including 1) Nature Exposure Scale, 2) Connectedness to Nature Scale, 3) Spiritual Values Scale, and 4) PWB Scale. For mediation test, data was analysed by employing Structural Equation Modeling (SEM) in AMOS version 23.0, and the results show that nature exposure can only significantly predict PWB through the mediation of spirituality. Whereas, connectedness to nature was found to have significant direct and indirect influence on PWB (through the mediation of spirituality). The model complies with the required model of fit standard (GFI= .903, AGFI= .880, CFI= .947, IFI= .948, NFI= .858, TLI= .940, RMSEA= .041). This study verified that to improve PWB among school students, exposing them to nature without the existence of spirituality is not sufficient to affect PWB. Whereas having a connectedness to nature can influence PWB with or without the presence of spirituality. This study recommends the implementation of the outdoor classroom, which involves teaching and learning in the setting of nature while inculcating spirituality might help students to not only excel in academics but also improve their PWB.